Efeito de diferentes tratamentos de superfície e da cimentação adesiva na característica de weibull, topografia de superfície e resistência à flexão de zircônias monolíticas translúcida e ultratranslúcida - Silva, Bianca Cristina Dantas (2023)
Objective: The objective of this work was to evaluate the effect of different surface treatments and adhesive cementation on the flexural strength of monolithic zirconia. Methodology: Translucent (3Y-TZP) (ZT) and ultratranslucent (5Y-PSZ) (ZUT) monolithic zirconia blocks were sectioned and 240 sintered bars measuring 8x2x1mm were obtained. The bars were divided into 16 groups (n=15) according to the factors “Zirconia” (ZT and ZUT), “Cementation” (Cem), and “surface treatment” (Ctr: Control, Al: Aluminum oxide/Al2O3 50µm, Si: Silica/SiO2 coated aluminum oxide, Gl: Glazing + hydrofluoric acid). Half of the bars received the application of a layer of adhesive followed by the application of a thin layer of resin cement and light curing (40s, 1200mW/cm2). After surface treatments, the groups without cementation (N=120, n=15) were submitted to the measurement of surface roughness with a digital roughness meter. All the bars were then submitted to the flexural strength (RM) test (ODEME-ISO150: 1.0 mm/min; 100 Kgf). Scanning electron microscopy (SEM) analysis was used for qualitative assessment of the fractured surface and surface morphology. RM and roughness data (µm) were statistically evaluated by 3- and 2-way ANOVA, respectively, followed by Tukey's test (5%) and Weibull analysis. Results: For roughness, glazing promoted greater smoothness compared to silicatization. Regarding the RM, for ZT, the sandblasted groups promoted a significant increase in the RM while the glazing reduced it. As for the ZUT, there was no statistical difference between the groups without cementation, however, among the cemented groups, ZUT.Si/Cem and ZUT.Al/Cem obtained MR superior to the other groups. Additionally, the Weibull modulus (m) was statistically different between the ZT and ZUT control groups; however, there was no statistical difference between the protocols for the same type of zirconia. Conclusion: For ZT, sandblasting with Al2O3 or SiO2 increases resistance, while the application of glaze tends to reduce it, regardless of cementation. As for the ZUT, the application of resin cement increases its resistance when associated with sandblasting with Al2O3 or SiO2. Despite this, sandblasting protocols promote greater surface roughness concerning glazing.